SULFUR ISOTOPIC STUDIES OF CONTINENTAL FLOOD BASALTS IN THE NORIL'SK REGION: IMPLICATIONS FOR THE ASSOCIATION BETWEEN LAVAS AND ORE-BEARING INTRUSIONS - Ripley E.M.; Li C.; Elswick E.R.; Lightfoot P.C. (My University, 2003)
Previous studies of both ore and non-ore-bearing intrusives in the Permo-Triassic flood basalts of the Siberian platform in the Noril’sk area have shown that high-grade Ni–Cu–platinum group elements (PGE) mineralization is associated with anomalously high δ34S values of ∼8 to 12‰. In addition, several researchers have proposed that observed depletions in the Cu, Ni, and PGE content of basaltic lavas of the Nadezhdinsky (Nd) Formation are related to diffusional exchange with, and upgrading in metal tenor of, sulfides in the volcanic conduit system. Sulfur isotopic studies of the lavas at Noril’sk were initiated to determine if interaction with crustally derived sulfur in the conduit system was evident, and if the Nd lavas in particular were characterized by an anomalous isotopic signature. δ34S values of the lavas range from −4.5 to 8.7‰ Vienna Cañon Diablo Troilite (VCDT), with S concentrations from <40 to 1373 ppm. The majority of δ34S values range from 0 to 4‰, and are similar to those from S-poor intrusions in the Noril’sk area. Although textural data are not supportive of early sulfide saturation and the presence of immiscible sulfide droplets in the lavas, recrystallization may have erased expected mineralogical and textural evidence. Mineralogical data indicate that hydrothermal alteration of the lavas has occurred, but S redistribution has been restricted to localized areas and δ34S values have not been affected. The relatively low S concentrations of the lavas are thought to be due in large part to degassing of the lavas in the shallow conduit system and during eruption. Our calculations are consistent with the premise that degassing of basaltic magmas at temperatures in excess of ~900°C at QFM leads to only minor 34S-depletion of sulfur remaining in the melt, and decreases in δ34S values of less than 2‰ at 90% degassing. For this reason all lavas with δ34S values in excess of ~ 2‰ require a contribution of 34S-enriched country rock sulfur. Because of the high S content and δ34S value (~ 16–20‰) of evaporites in the country rocks at Noril’sk, contamination of less than 0.5% is required to explain the most 34S-enriched lavas. The Nd lavas have an average δ34S of 2.9‰, but show no difference in S isotopic composition relative to the other lavas, suggesting that metal depletion involved only limited S transfer, or that exchange between mantle-derived S and S of crustal origin buffered δ34S values to less than ~5‰. Anomalously positive δ34S values, similar to those of the ore-bearing intrusives in the Noril’sk region, are not consistently found in low-S rocks, either lavas or intrusives. Although the mechanism for the derivation of sulfide in the ore-bearing intrusions remain speculative, it is clear that the formation of sulfide ores characterized by high metal tenors proceeded only in the presence of sulfur of crustal origin.